Registers of the Education System in European Countries: Useful Practices for Ukraine - Puhachova, M. V. (Statistics of Ukraine, 2021)
Education sectors at country level rely on the circulation of large scopes of information pertaining to education institutions, research institutions, pupils and students, teaching staff, researchers, education diploma or certificates etc. Therefore, the register systems allowing to systematize this information, file it in a convenient form, edit and communicate to physical persons whom these data belong, and to support administrative decision making constitute a necessary tool for the satisfaction of information needs of the modern society. The registers (databases) of the education sector are integral components of the online information resource system in developed countries, which usually consists of the two subsystems: registers containing information about the population, and business registers. The greatest progress in creating online information resource system, according to experts from international organizations, has been achieved in North European countries. These countries have also become pioneers in carrying out population censuses on the basis of registers, including ones in the education sector. The article’s objective is to sum up the practices of North European countries in creating and operating electronic information resource systems in the education sector for its adaptation in the Ukrainian realities. The education registers (databases) of Denmark, the Netherlands, Norway, and Estonia are discussed, with making comparison of register systems in six North European countries. It is stressed that Denmark has created the most elaborate register system operated by the line ministry and the statistical office, in the Netherlands and Norway only two education registers exist, containing the necessary information on all the education levels of the population, Estonia has the single information system for the education, and in Sweden and Finland separate registers for each education level have been created. All the above mentioned register systems in education have sufficient information content, and they are continuously improved. And most importantly, these education registers (databases) in all the studied countries are linked by personal identifiers of individuals with other registers containing information about the population. The process of creating the Unified State Electronic Database on Education in Ukraine is analyzed, with elaborating on the registers included in this system and their content. Conclusions and recommendations on improvements and further developments in education registers of Ukraine and their links with other population-specific registers are made by summing up the practices of creating electronic information resource systems in North European countries.